A lesion suspected of melanoma by dermoscopy: we must trust this diagnostic tool - Gurfinkel, Paula Cabral de Menezes (Specjalisci Dermatolodzy, 2013)
BACKGROUND: The incidence of cutaneous melanoma is increasing worldwide and early diagnosis is essential since the prognosis is poor in advanced stages of disease. Dermoscopy emerged as an additional and important diagnostic procedure for the early diagnosis of cutaneous melanoma. MAIN OBSERVATION: We report a case of a 52-year-old man, who developed a pigmented lesion in the right pretibial region. Dermoscopy highly suggestive of melanoma. The initial histopathological evaluation suggested a benign lesion. Since dermoscopy was very suspicious, a more extensive histopathological study of the excised skin fragment was performed. This led to a change of diagnosis to a melanoma with partial regression. CONCLUSIONS: The present case shows that occasionally dermoscopy may be more informative for diagnosis of melanoma than an initial histopathology result.